2009
DOI: 10.1098/rsbl.2008.0761
|View full text |Cite
|
Sign up to set email alerts
|

Sexual segregation of pelagic sharks and the potential threat from fisheries

Abstract: Large pelagic sharks are declining in abundance in many oceans owing to fisheries exploitation. What is not known however is whether withinspecies geographical segregation of the sexes exacerbates this as a consequence of differential exploitation by spatially focused fisheries. Here we show striking sexual segregation in the fastest swimming shark, the shortfin mako Isurus oxyrinchus, across the South Pacific Ocean. The novel finding of a sexual 'line in the sea' spans a historical longline-fishing intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 16 publications
7
137
0
1
Order By: Relevance
“…Strong segregation by size, sex and reproductive stage are well documented characteristics of most shark populations (Springer 1967;Sims 2005). Mucientes et al (2009), for example, reported strong sex segregation at large scales in the Pacific Ocean for shortfin mako (Isurus oxyrinchus) and suggested that differential exploitation of males was possible. Camhi et al (1998) also suggested selective take of males only as a potential management measure for sharks.…”
Section: Risk Mitigation Strategies In Multispecies Tropical Shark Fmentioning
confidence: 99%
“…Strong segregation by size, sex and reproductive stage are well documented characteristics of most shark populations (Springer 1967;Sims 2005). Mucientes et al (2009), for example, reported strong sex segregation at large scales in the Pacific Ocean for shortfin mako (Isurus oxyrinchus) and suggested that differential exploitation of males was possible. Camhi et al (1998) also suggested selective take of males only as a potential management measure for sharks.…”
Section: Risk Mitigation Strategies In Multispecies Tropical Shark Fmentioning
confidence: 99%
“…Hence, the large-scale, trans-national area occupied by juvenile blue sharks within this 'nursery' further complicates any future management or conservation initiatives (Baum et al 2003), which would require internationally coordinated action. Moreover, while the pattern appears complex, there is evidence that blue sharks exhibit age and sexual segregation in different regions of the North Atlantic, indicating different components of the population may face differential risk from fisheries depending on which geographical regions they occupy at specific times (Mucientes et al 2009). This may act to accelerate declines further.…”
Section: Fisheries and Conservationmentioning
confidence: 99%
“…Although sexual segregation for most pelagic species is of little interest, sexual segregation for sharks has attracted great interest because of the potential impacts on fisheries population dynamics and management (Mucientes et al 2009). None of the 7 species examined in this study showed sexual segregation in vertical habitat, as there were no significant differences in vertical distributions between genders.…”
Section: Implication Of Differences/similarities In Vertical Distribumentioning
confidence: 99%